Aktualisasi Nilai- Nilai Islam dalam "Gurindam Dua Belas" Karya Raja Ali Haji - Ahmad Bachmid (Buletin Al-Turas, 2005)
Raja Ali Haji (1809-1870) was a Malay poet born in Penyengat Island, Riau. His most popular work among the Nusantara poets is Gurindam Dua Belas that was adopted form Islamic teaching texts; Qur’an and Hadis. Gurindam Dua Belas consists of the essential Islamic teaching such as Iman, Islam, and Ihsan which is according to him is the same as Akhlak and Mu’amalah Duniawiyah.